Conditions, pathogenesis, and progression of diabetic kidney disease and early decliner in Japan. Issue 1 (22nd March 2020) - Yoshida, Yui; Kashiwabara, Kosuke; Hirakawa, Yosuke; Tanaka, Tetsuhiro; Noso, Shinsuke; Ikegami, Hiroshi; Ohsugi, Mitsuru; Ueki, Kohjiro; Mita, Tomoya; Watada, Hirotaka; Koya, Daisuke; Mise, Koki; et al.
Abstract : Objective: Glomerular filtration rate (GFR) decreases without or prior to the development of albuminuria in many patients with diabetes. Therefore, albuminuria and/or a low GFR in patients with diabetes is referred to as diabetic kidney disease (DKD). A certain proportion of patients with diabetes show a rapid progressive decline in renal function in a unidirectional manner and are termed early decliners. This study aimed to elucidate the prevalence of DKD and early decliners and clarify their risk factors. Research design and methods: This combination cross-sectional and cohort study included 2385 patients with diabetes from 15 hospitals. We defined DKD as a urinary albumin to creatinine ratio (ACR) ≥30 mg/gCr and/or estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m². We classified patients into four groups based on the presence or absence of albuminuria and a decrease in eGFR to reveal the risk factors for DKD. We also performed a trajectory analysis and specified the prevalence and risk factors of early decliners with sequential eGFR data of 1955 patients in five facilities. Results: Of our cohort, 52% had DKD. Above all, 12% with a low eGFR but no albuminuria had no traditional risk factors, such as elevated glycated hemoglobin, elevated blood pressure, or diabetic retinopathy in contrast to patients with albuminuria but normal eGFR. Additionally, 14% of our patients were early decliners. Older age, higher basal eGFR, higher ACR, and higher systolic blood pressure were significantly associated with early decliners. Conclusions: The prevalence of DKD in this cohort was larger than ever reported. By testing eGFR yearly and identifying risk factors in the early phase of diabetes, we can identify patients at high risk of developing end-stage renal disease.